Differentiating consumption contexts as a basis for diversity in food design education: Eating in or eating out?. (1st April 2017) - Schifferstein, Hendrik N. J.
Designers can play a significant role in providing the world population with food that is produced in a sustainable way, is tasty and healthy and can form the centrepiece in culinary experiences. However, design students will need to acquire more knowledge specific for the food domain if they want to qualify as cooperation partners for other food professionals. In addition, because the food domain is vast and diverse, food design education could focus on various application domains, resulting in design students with different profiles.In this article, I make a distinction between designing for a person who consumes food at home or is eating out. The first case emphasizes the food itself in the home situation, including food production, packaging, food buying, shelf life, preparation, serving, handling leftovers and waste disposal. In the second case, the consumer's meal experience depends on the atmosphere in the restaurant, interactions with serving staff, the offerings on the menu and quality of the dish. In addition, several processes take place outside the consumer's view, such as food preparation, storage, personnel management and business administration.Based on these topics and comparison with adjoining educational curricula, a list of training topics is derived. For all food designers, this consists of general design capabilities, food science, cooking skills, consumer insights and sustainability issues. In addition, the 'eating at home' designer should gather knowledge on agricultural production, food technology and food industry business, whereas the 'eating out' designer will need to focus mainly on food product knowledge, culinary technology, equipment engineering, restaurant design, consumer dining behaviour and hospitality business.